Effect of Storage of Eucalyptus hybrid Leaves on their Essential Oil - Shiva, M. P.; Jain, P. P.; Suri, R. K.; Ram, Jagat; Gulati, N. K. (Indian Forester, 1983)
The paper furnishes the details of chemical studies undertaken on that effect of storage of Eucalyptus hybrid leaves stored both in open and shade. The results revealed that there is no significant difference in the quality and quantity of oil recovered from leaves after storage and that the entrepreneurs can safely distill the oil from leaves conveniently if they are not able to recover the oil from leaves immediately after felling of trees in the forest.